The experience of moral distress in nursing: the nurses’ perception - Barlem, Edison Luiz Devos (2012)
With the objective to understand the nurses’ perception of moral distress, as well as its frequency and intensity, this study used a survey utilizing a six-point Likert scale, with 124 nurses working in hospitals in southern Brazil in 2008. Using a self-administered questionnaire and factorial analysis, four constructs were identified and validated. The final results were obtained through three different analyses: 1) descriptive statistical analysis; 2) analysis of variance; and 3) multiple regression. The construct that showed the highest intensity of perception regarding moral distress was the lack of competency in the work team (4.55), followed by the nurse’s denial of their role as patient advocate (4.30), therapeutic obstinacy (3.60) and disrespecting the patient’s autonomy (3.57). Regarding the perception of the frequency of moral distress, once again, the highlighted construct was the lack of competency within the work team (2.42), followed by therapeutic obstinacy (2.26), the nurse’s denial of their role as patient advocate (1.71) and disrespecting the patient’s autonomy (1.42).